Efficiency of medical and physical rehabilitation in patients who suffered from cerebral ischemic stroke - Koziolkin, O. A.; Miedviedkova, S. O.; Shevchenko, L. O.; Liakhova, І. М.; Malakhova, S. M.; Lisova, O. O.; Cherepok, О. О.; Козьолкін, Олександр Анатолійович; Мєдвєдкова, Світлана Олександрівна; Шевченко, Людмила Олександрівна; Ляхова, Інна Миколаївна; Малахова, Світлана Миколаївна; et al. (Запорізький державний медичний університет, 2019)
Objective. The purpose is to increase the efficiency of medical and physical rehabilitation in patients who suffered from cerebral ischemic stroke (CIS) with the help of differentiated use of rehabilitation measures depending on the severity of neurological disorders and comorbid states. Materials and methods. In the clinic of nerve diseases of Zaporizhzhia State Medical University we observed 305 patients (213 men and 92 women, average age is 57.93 ± 0.43 years old) in the recovery period of CIS. All patients were clinically and neurologically examined according to a specially designed protocol using modern scales – NIHSS, mRS on the 10th, 30th, 90th and 180th day of the disease and differentiated treatment in accordance with standards and protocols for the assistance to patients who suffer from stroke. Patients with CIS were divided into four groups. The first group included 111 patients (36.4 %) with CIS, among whom the severity of post-stroke disorders was mild (state on NIHSS ≤ 7 points), without comorbid condi¬tions. The second group consisted of 120 patients (39.3 %) also with a mild degree of post-stroke disorders (state on NIHSS ≤7 points) and the comorbidity (heart pathology, diabetes mellitus, chronic obstructive pulmonary disease of the IInd stage). The third group included 36 patients (11.8 %) with CIS, among whom the severity of post-stroke disorders was moderate and obvious (state on NIHSS > 7 points), without comorbidity. The fourth group consisted of 38 patients (12,5 %) with moderate and severe post-stroke disorders (state on NIHSS > 7 points) and comorbid pathology. Statistical analysis was carried out using descriptive statistics methods. The interrelation between qualitative features was evaluated according to the criterion of the Pearson’s chi-square test. Results. As a result of the treatment among the patients in group I, 97 patients (87.4 %) (index mRS 0–2) had a favorable outcome, relatively favourable one (index mRS ≥3 points) – only 14 (12.6 %); In group II, 104 patients (86.7 %) achieved favorable treatment, relatively favorable one – 16 (13.3 %); in group III – a favorable outcome was recorded in 13 patients (36.1 %), relatively favorable – in 23 (63.9 %), and in group IV – a favorable outcome was revealed in 13 patients (34.2 %), relatively favorable one – in 25 (65.8 %). Conclusions. The differentiated application of medical and physical rehabilitation in patients with CIS in different groups, taking into account the individual prognosis of the recovery period and selection of methods and ways of treatment, has improved significantly the effectiveness of rehabilitation measures. Мета роботи – підвищити ефективність медичної та фізичної реабілітації у хворих, які перенесли мозковий ішемічний інсульт (МІІ), шляхом диференційованого застосування реабілітаційних заходів залежно від тяжкості неврологічних розладів і наявності коморбідних станів. Матеріали та методи. У клініці нервових хвороб Запорізького державного медичного університету під нашим спостере¬женням перебували 305 хворих (213 чоловіків і 92 жінки, середній вік – 57,93 ± 0,43 року) у відновному періоді МІІ. Усім хворим виконали клініко-неврологічне дослідження за спеціально розробленим протоколом, використовуючи сучасні шкали (NIHSS, mRS) на 10, 30, 90 і 180 добу захворювання, а також диференційоване лікування за стандартами та протоколами надання допомоги хворим на інсульт. Пацієнтів із МІІ поділили на 4 групи. У I групу ввійшли 111 (36,4 %) пацієнтів із МІІ, в яких був легкий ступінь вираженості післяінсультних розладів (стан за NIHSS ≤7 балів), без комор¬бідних станів. II групу становили 120 (39,3 %) пацієнтів із легким ступенем післяінсультних розладів (стан за NIHSS ≤ 7 балів) і наявністю коморбідної патології (патологія серця, цукровий діабет, хронічне обструктивне захворювання легень II cтадії). У III групу ввійшли 36 (11,8 %) хворих на МІІ, в яких ступінь вираженості післяінсультних розладів був помірним і вираженим (стан за NIHSS > 7 балів), без коморбідної патології. IV група – 38 (12,5 %) хворих із помірними та вираженими післяінсультними розладами (стан за NIHSS >7 балів) і коморбідною патологією. Статистичний аналіз виконали, використовуючи методи описової статистики. Наявність взаємозв’язку між якісними ознаками оцінювали за критерієм хі-квадрат Пірсона. Результати. У результаті лікування хворих I групи сприятливий результат (значення mRS 0–2 бали) мали 97 (87,4 %) пацієнтів, відносно сприятливий (значення mRS ≥ 3 бали) – тільки 14 (12,6 %); у II групі сприятливий наслідок визна¬чили у 104 (86,7 %) пацієнтів, відносно сприятливий – у 16 (13,3 %); у III групі сприятливий результат зафіксували у 13 (36,1 %) пацієнтів, відносно сприятливий – у 23 (63,9 %); у IV групі сприятливий наслідок встановили у 13 (34,2 %) пацієнтів, відносно сприятливий – у 25 (65,8 %). Висновки. Диференційоване застосування медичної та фізичної реабілітації у хворих на МІІ у різних групах з ураху¬ванням індивідуального прогнозу результату відновного періоду та підбором методів і способів лікування дали змогу суттєво підвищити ефективність реабілітаційних заходів. Цель работы – повысить эффективность медицинской и физической реабилитации у больных, перенесших мозговой ишемический инсульт (МИИ), путем дифференцированного применения реабилитационных мероприятий в зависимости от тяжести неврологических расстройств и наличии коморбидных состояний. Материалы и методы. В клинике нервных болезней Запорожского государственного медицинского университета под наблюдением находились 305 больных (213 мужчин и 92 женщины, средний возраст – 57,93 ± 0,43 года) в вос¬становительном периоде МИИ. Всем больным проводили клинико-неврологическое исследование по специально разработанному протоколу с использованием современных шкал (NIHSS, mRS) на 10, 30, 90 и 180 сутки заболевания и дифференцированное лечение согласно стандартов и протоколов оказания помощи больным инсультом. Пациенты с МИИ разделены на 4 группы. В I группу вошли 111 (36,4 %) пациентов с МИИ, у которых степень выраженности постинсультных расстройств была легкая (состояние по NIHSS ≤ 7 баллов), без коморбидных состояний. II группа состояла с 120 (39,3 %) пациентов, также с легкой степенью постинсультных расстройств (состояние по NIHSS ≤ 7 баллов) и наличием коморбидной патологии (патология сердца, сахарный диабет, хроническое обструктивное заболевание легких II cтадии). В III группу вошли 36 (11,8 %) больных с МИИ, у которых степень выраженности постинсультных расстройств была умеренная и выраженная (состояние по NIHSS >7 баллов), без коморбидной патологии. IV группу составили 38 (12,5 %) больных с умеренными и выраженными постинсультными расстройствами (состояние по NIHSS >7 баллов) и коморбидной патологией. Статистический анализ проведен с использованием методов описательной статистики. Наличие взаимосвязи между качественными признаками оценивали по критерию хи-квадрат Пирсона. Результаты. В результате лечения больных I группы благоприятный исход (значение mRS 0–2 балла) имели 97 (87,4 %) пациентов, относительно благоприятный (значение mRS ≥ 3 балла) – только 14 (12,6 %); во II группе благоприятный исход был у 104 (86,7 %) пациентов, относительно благоприятный – у 16 (13,3 %); в III группе благоприятный исход зафиксирован у 13 (36,1 %) пациентов, относительно благоприятный – у 23 (63,9 %), а в IV группе благоприятный исход отмечен у 13 (34,2 %) пациентов, относительно благоприятный – у 25 (65,8 %). Выводы. Дифференцированное применение медицинской и физической реабилитации у больных МИИ в разных группах с учетом индивидуального прогноза выхода восстановительного периода и подбором методов, способов лечения позволило значительно повысить эффективность реабилитационных мероприятий.
Ефективність медичної та фізичної реабілітації у хворих, які перенесли мозковий ішемічний інсульт
Эффективность медицинской и физической реабилитации у больных, перенесших мозговой ишемический инсульт
Keywords: stroke; stroke rehabilitation; інсульт; реабілітація інсульту; инсульт; реабилитация инсульта